Histoplasmosis in Sri Lanka - a masquerader in a strange land: A Case Report - M. N. Jayawardena; K. Siriwardane; P. Jayasooriya; S. Sigera; P. Jayasekera (Sri Lankan Journal of Infectious Diseases, 2019)
We present a patient with an oral mucosal ulcer who was diagnosed with disseminated histoplasmosis. This fungal infection is endemic in the United States, and thus may be not considered in the differential diagnosis of oral ulcers in Sri Lanka. Furthermore, it may mimic many common diseases found in Sri Lanka. It is therefore important to be aware of this entity, since it is potentially curable if diagnosed and treated early.